Visualizing semipermeability of the cell membrane using a pH-responsive ratiometric AIEgen. Issue 22 (26th May 2020) - Gu, Yuan; Zhao, Zheng; Niu, Guangle; Zhang, Han; Wang, Yiming; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Tang, Ben Zhong
Abstract : By utilizing a pH-responsive ratiometric AIEgen, dihydro berberine (dhBBR), ion trapping phenomenon was successfully visualized. Abstract : In clinical chemotherapy, some basic drugs cannot enter the hydrophobic cell membrane because of ionization in the acidic tumor microenvironment, a phenomenon known as ion trapping. In this study, we developed a method to visualize this ion trapping phenomenon by utilizing a pH-responsive ratiometric AIEgen, dihydro berberine (dhBBR ). By observing the intracellular fluorescence of dhBBR, we found that non-ionized dhBBR can enter cells more easily than ionized forms, which is in accordance with the concept of ion trapping. In addition, dhBBR shows superior anti-photobleaching ability to Curcumin thanks to its AIE properties. These results suggest that dhBBR can serve as a bioprobe for ion trapping.